2006
DOI: 10.1093/jee/99.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluations of Systemic Insecticides for Control of Anoplophora glabripennis (Coleoptera: Cerambycidae) in China

Abstract: Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae), a pest native to China and Korea, was discovered in North America in 1996. Currently, the only reliable strategy available for eradication and control is to cut and chip all infested trees. We evaluated various doses of the systemic insecticides azadirachtin, emamectin benzoate, imidacloprid, and thiacloprid for control of A. glabripennis in naturally infested elms (Ulmus spp.), poplars (Populus spp.), and willows (Salix spp. ) in China between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…P. nigra trees in China. Poland et al (2006b) reported 1-2 ppm in the leaves and twigs of 9.6 ± 0.2 cm diam. Salix matsudana Koidz trees 1 month postinjection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. nigra trees in China. Poland et al (2006b) reported 1-2 ppm in the leaves and twigs of 9.6 ± 0.2 cm diam. Salix matsudana Koidz trees 1 month postinjection.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has relied exclusively on the systemic insecticide imidacloprid, a neonicotinoid that can be injected directly into tree trunks or into the soil for uptake into the vascular system via roots (Wang et al, 2005;Poland et al, 2006b). ALB are known to be affected by imidacloprid during their normal feeding on the bark of twigs of imidacloprid-treated trees, although imidacloprid concentrations in bark alone have not been reported (Wang et al, 2005;Poland et al, 2006b). …”
Section: Introductionmentioning
confidence: 99%
“…Because of its great economic loss and the threat posed by A. glabripennis, a large number of research projects have focused on this beetle in recent years and great progress has been made in many respects (Zhang et al, 2002(Zhang et al, , 2003Haack, 2003;Luo et al, 2003;Keena 2005Keena , 2006Poland et al, 2006aPoland et al, , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…A large part of the debate on injection is not about the possible harmful consequences M. Ferry and S. Gomez for the health of the treated tree with this technique but about its efficacy and cost [29,31,[60][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Controversy On the Injection Technique In Treesmentioning
confidence: 99%